Breastfeeding and COVID-19: From Nutrition to Immunity - Vassilopoulou, Emilia; Feketea, Gavriela; Koumbi, Lemonica; Mesiari, Christina; Berghea, Elena Camelia; Konstantinou, George N. (Frontiers in Immunology, 2021)
Breastfeeding not only provides the optimum source of nutrients for the neonate, and its first strong shield against infection, but it also lays the foundation for somatic and psychological bonding between mother and child. During the current COVID-19 pandemic, although the guidelines of the relevant international and national agencies recommend breastfeeding by SARS-CoV-2 infected mothers, considerable insecurity persists in daily clinical practice regarding the safety of the infants and the perceivec advantages and disadvantages of discontinuation of breastfeeding. This is a systematic review of the currently available information regarding the transmissibility of SARS-CoV-2 through or while breastfeeding, and the protection against infection that breast milk might provide. The accumulated body of knowledge regarding the role of breast milk in the development of the neonatal immune system and protection against infection by other respiratory viruses is discussed, with a focus on the anti-inflammatory role of the antibodies, microbes and viruses provided to the infant in breast milk, and its relevance to the case of SARS-CoV-2.